To Be Rational or Not to Be: An Explication and Appraisal of the Shī‘ī Correlation Principle Controversy - Rāsiḫ, Muḥammad (Interdisciplinary journal for religion and transformation in contemporary society, 2021)
Abstract Rationalist Imāmī Shī‘ī’s attempt to deal with problems with which the Muslim society grapples on the basis of the rational potentialities of Shī‘ī jurisprudence. It refers to the claim of correlation between rulings dictated by human reason and those commanded by the divine texts. Certain scholars have attempted to offer a partial support of the rationalist stance. They try to show a middle way by which reason and the text may be kept under the same roof. Nevertheless, it does not seem that the partial defence works. Hence, a number of scholars have endeavoured to put forth a theory of identity of Shar ‘ and reason. In this study, negative and positive arguments shall be introduced and appraised so that a justifiable conclusion on the issue may be offered. Overall, the breakthrough appears to lie in the different field of theories of axiology and religion, rather than jurisprudential reasoning and theology.